Gardening alchemy : 80 recipes and concoctions for organic fertilizers, plant elixirs, potting mixes, pest deterrents, and more - Rose, Stephanie (Gardener) (Cool Springs Press, 2020)
"Garden Alchemy is filled with recipes and instructions for making homemade versions of dozens of gardening products, including fertilizers, pest deterrents, potting soils, and more"--